2018
DOI: 10.1177/1475725718810181
|View full text |Cite
|
Sign up to set email alerts
|

An Open versus Traditional Psychology Textbook: Student Performance, Perceptions, and Use

Abstract: In the current study we examined students' course performance, perceptions, and self-reported use of an open textbook compared to a traditional publisher's textbook in an introductory psychology course. Sixty students from two course sections used either an open textbook or a traditional textbook. To minimize the effect of confounding variables, each section was taught by the same instructor, at the same time of day, using identical in-class materials, syllabi, and sequencing, on alternating days of the week. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 23 publications
2
23
1
Order By: Relevance
“…Given the inherent difficulties of conducting research in the classroom, methodological limitations may have contributed to the mixed outcomes of this work (e.g., lack of inferential statistics, Hilton and Laman, 2012; small sample sizes, Grissett and Huffman, 2019). For example, some studies compare classes taught by instructors over multiple semesters (e.g., Hilton and Laman, 2012;Clinton, 2018;Grissett and Huffman, 2019) rather than comparing classes taught by different instructors in the same semester. While the former approach is beneficial because it controls for possible differences in instructor variables (such as experience or enthusiasm), it may confound differences in students' performance across semesters.…”
Section: Introductionmentioning
confidence: 99%
“…Given the inherent difficulties of conducting research in the classroom, methodological limitations may have contributed to the mixed outcomes of this work (e.g., lack of inferential statistics, Hilton and Laman, 2012; small sample sizes, Grissett and Huffman, 2019). For example, some studies compare classes taught by instructors over multiple semesters (e.g., Hilton and Laman, 2012;Clinton, 2018;Grissett and Huffman, 2019) rather than comparing classes taught by different instructors in the same semester. While the former approach is beneficial because it controls for possible differences in instructor variables (such as experience or enthusiasm), it may confound differences in students' performance across semesters.…”
Section: Introductionmentioning
confidence: 99%
“…Hilton et al (2013) found test scores virtually unchanged in mathematics courses, and a summary of nine efficacy studies showed mostly nonsignificant differences when OER were used (Hilton, 2016). Additionally, two studies in psychology courses compared two different textbooks within the same course and found no significant differences in exam scores (Durwin and Sherman, 2008; Grisset and Huffman, 2018). Our results add to this body of research by focusing on student outcomes in a single community and technical college biology course.…”
Section: Resultsmentioning
confidence: 99%
“…They compared the results of students enrolled in the course and found that pass rates increased slightly when all courses used OER. Finally, Grisset and Huffman (2018) tested an open and published textbook in a psychology class at a small public university. Similarly, they found no significant differences in exam scores or course grades.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, using OER in educational settings has also gained the attention of researchers, leading to studies on the effectiveness of OER, teacher and learner perceptions of these materials, and their related benefits. To date, studies have promulgated that OER are positively perceived by teachers and instructors, and that they are as effective as traditional or commercial textbooks and materials (Hilton 2016;Hilton 2020;Delgado et al 2019;Shams et al 2020;Orton Grissett and Huffman 2019).…”
Section: Introductionmentioning
confidence: 99%